Multi Agent-Based Control Techniques to Reduce Losses for Smart Grid Connected Microgrids - Sen, Gorkem; Baysal, Mustafa (IEEE, 2018)
In this paper, two agent-based control techniques for control and management of smart grid (SG) connected microgrid (MG) are proposed to reduce losses; decentralized and hybrid control strategies. Proposed strategies are implemented through a multi agent system (MAS) framework in which MG consists of a two-layer control structure. The first layer is the medium voltage distribution network and the second layer is the communication network between agents. A systematic method has been used in both strategies, which can be used to derive a set of control law for agents from communication network. Also, output power supplied by distributed generations satisfies load demands in SG when agents use control law. Control strategies are tested on a modified IEEE 13-bus test feeder which is modelled in MATLAB-Simulink (TM). The simulation results for the modified test system are presented to demonstrate the effectiveness of proposed control strategies and to compare them.
Keywords: Distributed generation; microgrid (MG); multi agent system (MAS); smart grid; systematic method; Computer Science; Engineering